Impact of information and communication technologies on agricultural households’ welfare in Benin - Nonvide, Gbêtondji Melaine Armel (My University, 2023)
Information technologies are very important to transform the agricultural sector and improve economic performance. Nevertheless, does the use of information and communication technologies (ICT) improve agricultural households’ welfare? To answer this, the study used a nationally representative household survey, the Comprehensive Food Security and Vulnerability Analysis (CFSVA) carried out in 2017 in Benin. The survey covered a sample of 15 000 households, however, the analysis focused on the 6502 agricultural households. An endogenous switching regression model was employed to control for selection bias and endogeneity issues. Results indicated that the use of ICT increases households’ consumption expenditure by 89.6%. This implies that the use of ICT improves agricultural households’ welfare. Other variables that affect agricultural households’ welfare include age, marital status, farm size, access to credit, ownership of livestock, membership in a farmer-based organization, and region of residence. Furthermore, the decision to use ICT in agricultural households depends on the level of education, age, sex, marital status, farm size, access to credit, ownership of livestock, membership in a farmer based organization, and location. These findings suggest that policies that promote the use of ICT are key to improving welfare of agricultural households in Benin. These policies must consider demographic, socio-economic, and institutional characteristics of households.
Keywords: Agricultural households; Information and communication technologies; Endogenous switching regression model; Welfare; Benin